Anthropogenic noise affects winter song structure of a long-distance migrant, Gambel's white-crowned sparrow. Issue 1 (12th February 2020) - Phillips, Jennifer N; Katti, Madhusudan
Abstract: Many animals learn to produce acoustic signals that are used to attract mates and defend territories. The structure of these signals can be influenced by external features of the environment, including the anthropogenic soundscape. In many sedentary species, habitat features and soundscape appears to influence the cultural evolution of songs, often with tradeoffs for better transmission over sexually selected song structure. However, none have investigated whether noise on the wintering grounds affects song structure, which for long-distance migrants may result in an acoustic 'mismatch' when returning to a breeding ground. This study investigates urban noise effects on song structure in a long-distance migrant, Zonotrichia leucophrys gambelii, on the wintering grounds in the Fresno Clovis Metropolitan Area and in outlying non-urban areas. Songs and background noise levels were recorded concurrently, and song measurements of frequency and duration were examined differences across noise levels and habitats . We found that the buzz and trill decrease in bandwidth in the presence of noise. The length of the whistle and buzz portion of the song also tends to decreases with noise in urban habitats. This trend toward short, pure tones in noisy areas may transmit better in noisy urban winter habitats, but may not be adaptive on quieter breeding grounds. We suggest that future studies should consider whether winter auditory feedback and song learning environments have consequences for song crystallization and breeding success for long-distance migrants.